Deposition of Polycrystalline Diamond Films with a Controlled Grain Size by Periodic Secondary Nucleation; Materials Today: Proceedings; Vol. 3, supl. 2 : Diamond and Carbon Materials - DCM 2014 - Linnik S. A. Stepan Andreevich (2016, 2016)
Title screen